ANALYSIS OF THE ECB MONETARY POLICY MATCH FOR THE NEEDS OF THE EURO AREA COUNTRIES NEEDS - Reichenbachas, Tomas (Ekonomika, 2013)
Abstract. In this paper, using the Taylor rule (Taylor, 1993), the European Central Bank (ECB) monetary policy in 2000–2012, as well as individual interest rate needs of the euro area (EA) countries are analysed. It is assumed that the estimated Taylor rule interest rates are optimal for individual members. We have analysed whether the actual ECB interest rates and the calculated rates are different and have become more balanced towards individual countries’ needs. The work focuses attention on the last period (2008–2012) when the EA faced economic problems and an asymmetric shock. The analysis shows controversial results: on the one hand, the interest deviation mean decreases (just a little), but an increasing gap between individual needs can be seen: some countries are becoming increasingly divorced from the general EA needs. It makes them very vulnerable, and there is a risk that these countries in the face of asymmetric challenges can be “left behind” by the ECB focusing on the EA as a whole. Also, in this paper, the stationarity of the calculated deviations is analysed to help understand their nature. This approach is new, and the author is unaware of similar works. Analysis of the optimal interest rate dynamics has revealed that Germany needed the interest rates that were opposite to the needs of Spain and Greece and susceptible to divergence, so this led to the ECB difficulties in determining the proper interest for all countries’ needs. The EA as a currency area is most optimal for Belgium, Cyprus, Finland, France, Italy, and the Netherlands from the interest rate setting perspective.Key words: the Taylor rule, optimal monetary policy, asymmetric shocks, optimal currency area